The Association of Pension Income with the Incidence of Type I Obesity among Retired Israelis - Yuval Arbel; Chaim Fialkoff; Amichai Kerner (Journal of Obesity)
Previous studies have identified obesity and overweight as the fourth leading risk factor for global mortality. The objective of the current study is to investigate gender differences and the impact of wealth and income from pensions, sociodemographic variables, and self-assessment of health conditions on the projected probability to become obese in the postretirement age (67 years and older). We are unaware of previous studies, which explored the direct relationship between obesity, monetary income from pensions, wealth, and self-assessment of health conditions. To conduct this research, we make use of an extensive questionnaire concerning the economic and sociodemographic features and health and housing conditions of individuals administered within the framework of the 2015-2016 longitudinal survey conducted by the Israeli Central Bureau of Statistics (CBS). The survey is representative of the Israeli population and also includes information regarding the weight, height, gender, and age of each household member. Results of our study demonstrate that while for the female respondents older than 67, the projected probability of type I obesity (BMI ≥ 30) drops by 0.41% (p=0.0021) to 0.52% (p=0.0001) with an incremental 10,000 NIS (about $2,500) rise of gross annual income from a pension, for the male respondents above 67 years, the projected probability remains unchanged (p=0.4225). This outcome remains robust even when the 2015 BMI measurement of type I obesity (BMI ≥ 30) is controlled. This drop among women attenuates with a cutoff point increase from BMI ≥ 25 (overweight) to BMI ≥ 30 (type I obesity) to BMI ≥ 35 (type II obesity). Further results indicate that for both genders above 67 years and for men above 62 years, the projected BMI drop of one year decreases with income from a pension (p=0.013, p=0.039, and p=0.007, respectively), although the spread around the projection becomes wider. Compared with other martial status categories, for widowed females, the projected probability of obesity and self-reporting on improved health conditions drops by 6.58% (p=0.0419) to 11.28% (p=0.0048) and 6.55% (p=0.0190) to 7.47% (p=0.0036), respectively. For females older than 67, family status divorced drops the projected probability of obesity by 9.25% (p=0.0319). For males older than 67, results show a rise in projected obesity with car ownership by 6.10% (p=0.0897) to 6.41% (p=0.0469) and a drop in projected obesity with academic degree status by 9.93% (p=0.0106) to 10.14% (p=0.0118) and immigration status from American-European countries by 7.67% (p=0.0821) to 8.99% (p=0.0398) and Asian-African countries by 11.63% (p=0.0245) to 11.99% (p=0.02). Research findings stress the differences and similarities in male-female patterns of obesity after the retirement age of 67 years and may be of assistance to welfare and public health experts.